Malaria in Pregnancy: Knowledge, Attitudes, Perceptions, and Preventive Practices Among Pregnant Women in Okitipupa, Ondo State, Nigeria - Adeyemi Ogedengbe Omoge; Olabode Oluyinka Kayode (The Journal of Medicine, Law & Public Health, 2026)
Background: Malaria in pregnancy (MiP) remains a major public health concern in sub-Saharan Africa, contributing substantially to maternal and neonatal morbidity and mortality. Understanding and enhancing pregnant women's knowledge, attitudes, perceptions, and preventive practices in this regard is essential for improving malaria prevention and control. Objectives: This study assessed the knowledge, attitudes, and perceptions (KAP), as well as preventive practices regarding MiP among pregnant women attending antenatal clinics in Okitipupa, Ondo State, Nigeria. Methods: A descriptive cross-sectional study was conducted among 165 pregnant women attending antenatal clinics at two health facilities in Okitipupa, using a multistage sampling technique. Descriptive statistics summarised respondents' characteristics and KAP responses. Results: The respondents’ mean age was 28.6 ± 5.1 years, with most (66.1%) aged 26–35 years. Nearly all respondents (95.2%) had heard of malaria in pregnancy, while 92.7% correctly identified mosquito bites as the primary mode of transmission. Most participants recognised the seriousness of MiP and the protective roles of insecticide-treated nets (91.5%) and intermittent preventive treatment with sulfadoxine-pyrimethamine (83.0%). Nevertheless, misconceptions persisted regarding malaria transmission, self-medication, and the use of herbal remedies. Preventive attitudes were generally positive, although reported practices were not always consistent with respondents' knowledge. Conclusion: Pregnant women attending antenatal clinics in Okitipupa demonstrated generally good knowledge and positive attitudes towards malaria in pregnancy. However, persistent misconceptions and inappropriate preventive and treatment practices indicate the need for strengthened antenatal health education, culturally appropriate behaviour change communication, and sustained community engagement to improve maternal and neonatal health outcomes.